Desmoid-type Fibromatosis of the Mesentery: A Case Report - Tatyana Betova; Savelina Popovska; Radoslav Trifonov; Konstantina Karakadieva; Genoveva Valcheva; Lachezar Tanchev (Journal of Biomedical & Clinical Research)
Desmoid-type fibromatosis is a rare mesenchymal neoplasm with locally aggressive, infiltrating and destructive growth that is not characterized by a metastatic potential. According to their anatomical position, desmoid-type fibromatoses can be divided into three groups: extra-abdominal, intra-abdominal, and fibromatoses of the abdominal wall. Mesenteric fibromatoses account for 8% of the intra-abdominal ones. The latter are characterized by myofibroblastic proliferation and infiltration of both the pelvic and abdominal organs. We report a 26-year-old woman who complained of abdominal enlargement, feeling of heaviness, discomfort and reflux, which symptoms dated back 1-2 months prior to hospitalization. The patient underwent laparotomy due to subocclusive symptoms. Intraoperatively, a tumor sized 30 cm in diameter was found. The tumor originated from the mesentery and infiltrated in the jejunum, the entire ileum, and part of the caecum with perforation towards the abdominal cavity. The histological and immunohistochemical examinations are important for clarification of the diagnosis. The treatment requires a multidisciplinary approach, in which the surgical method has the key role.